Deciphering the response of asymmetry in the hydrophobic chains of novel cationic lipids towards biological function. Issue 3 (3rd January 2020) - Mukherjee, Dipanjan; Singh, Priya; Rakshit, Tatini; Puthiya-Purayil, Theja P.; Vemula, Praveen Kumar; Sengupta, Jhimli; Das, Ranjan; Pal, Samir Kumar
Abstract : Variations in molecular architecture of the hydrophobic tails of cationic lipids influence cationic liposome*s efficiency of delivering nucleic acids during cell transfection. Abstract : Cationic liposomes, a type of non-viral vectors, often play the important biological function of delivering nucleic acids during cell transfection. Variations in the molecular architecture of di-alkyl dihydroxy ethyl ammonium chloride-based cationic lipids involving hydrophobic tails have been found to influence their biological function in terms of cell transfection efficiency. For example, liposomes based on a cationic lipid (Lip1814) with asymmetry in the hydrophobic chains were found to display higher transfection efficacy in cultured mammalian cell lines than those comprising of symmetric Lip1818 or asymmetric Lip1810. The effect of variations in the molecular architecture of the cationic lipids on the biological activity of liposomes has been explored here via the photophysical studies of 8-anilino-1-naphthalenesulphonate (ANS) and Nile Red (NR) in three cationic liposomes, namely Lip1810, Lip1814 and Lip1818. Time-resolved fluorescence of ANS revealed reduced hydration at the lipid–water interface and enhanced relaxation dynamics of surface water (lipid headgroup bound water molecules) in Lip1810- and Lip1814-based liposomes in the presence of cholesterol. As the probe ANS failed to be incorporated into the lipid–water interface of Lip1818 due to the significantly high rigidity of these liposomes, no information concerning the extent of hydration of the lipid–water interface or the interfacial water dynamics could be obtained. Time-resolved polarization-gated anisotropy measurements of NR in the presence of cholesterol revealed the rigidity of the cationic liposomes to be increasing in the order of Lip1810 < Lip1814 < Lip1818. In the presence of cholesterol, moderately higher rigidity, reduced membrane hydration and enhanced relaxation dynamics of the interfacial water molecules gave rise to the superior cell transfection efficacy of Lip1814-based cationic liposomes than those of the highly flexible Lip1810 or the highly rigid Lip1818.